Traumatic oral fibroma of unusual size: a case report - Ramírez Suarez, Reynier (2025)
Traumatic fibromas are frequently found in the oral cavity. They are characterized by a localized proliferation of dense collagen fibers resulting from regional trauma, rather than representing a true neoplasm. This case report describes a patient with a clinical and histopathological diagnosis of traumatic fibroma, in which the lesion presented a considerable and unusual growth, leading to facial asymmetry. The lesion, with several months of evolution, showed a significant size, for which the therapeutic approach consisted of total excision. After one year of follow-up, there was no recurrence of the lesion. Surgical excision was considered for the treatment of traumatic oral fibroma. It is concluded that it is important to identify the etiologic factor and proceed with its elimination to avoid recurrence.